Pengaruh Pemasaran Produk Gadai Emas Di Bank Syariah Indonesia Terhadap Minat Nasabah Kantor Cabang Pembantu Medan Imam Bonjol - Jihan Suwifania; Tuti Anggraini (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Pawning gold is one of the products offered by Bank Syariah Indonesia Medan Imam Bonjol Sub-Branch Office which seeks to help the community in terms of funding. Marketing is still weak in terms of selling gold pawned goods as a result, no one really knows or understands what gold pawning is. This research was developed using qualitative research methods such as conducting interviews, data observation, and literature review. Based on research findings, gold pawn income continues to increase every year. To attract customers, Bank Syariah Indonesia Medan Imam Bonjol Sub-Branch Office is holding a promotion in the form of distributing prizes or knick-knacks if a certain amount of money has been withdrawn.